Technologie, milieu et travail vivant L’écologie politique à travers Simondon, Canguilhem et Schwartz - Angelini, Andrea (Mechane, 2023)
Simondonian thesis on the relationship between technique and nature, or between technological development and living activity, show several ambiguities already noted by the critical literature. These ambiguities evidently concern the possibilities and limits of an interaction between Simondon’s thought and the contemporary debate on ecology, in the light of a historical context – known as the Anthropocene, Technocene or Capitalocene – which raise, in new forms, the problem of the relationship between social forms of production and their bioenvironmental conditions of existence. In this article, we will examine the similarities and differences between the Simondonian and Canguilhemian assumptions on technical activity, its biological and somatic genesis and its relationship to the environment. By this confrontation, we will analyze the arguments of Yves Schwartz – and his relaunch of the biological philosophy of technique – to improve the theory of labour that Canguilhem sketched on the basis of the work of Georges Friedmann. This triangulation of readings will lead us to consider the structural relationship between techniques, body, society and environment, in order to question the mode of technological production as a collective and historical way of living, producing and inhabiting a heterogeneous biogeographic space.